Naphtha reforming catalyst as well as preparation method and application thereof

By preparing a Pt-Sn-Ce naphtha reforming catalyst with strong interaction, the problem of platinum atom aggregation of existing catalysts under high harsh conditions is solved, and the effects of high selectivity, long life and high efficiency liquid collection are achieved. .

CN119386904AActive Publication Date: 2025-02-07PETROCHINA CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202310935064.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2025-02-07
Estimated Expiration
2043-07-27

AI Technical Summary

Technical Problem

Under high-strength operating conditions, platinum atoms in existing reforming catalysts are prone to aggregation, resulting in poor product selectivity and shortening of the catalyst service life, making it difficult to meet the high-strength reaction process requirements of naphtha catalytic reforming.

Method used

By preparing an alumina carrier containing Sn or Sn and Ce and calcining in an atmosphere without oxygen, an alumina carrier with strong defect positions is formed. Then, Pt, Ce and competitive adsorbent are introduced using an impregnation liquid and dried , activation and reduction treatment to prepare a Pt-Sn-Ce naphtha reforming catalyst with strong interactions.

Benefits of technology

In high-temperature reaction, the Pt atoms do not easily accumulate, maintain good selectivity, high liquid collection, less dry gas and coke generation, good catalyst stability, long service life, and can meet the needs of high-strength reaction processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004367920610000081
    Figure BDA0004367920610000081
  • Figure BDA0004367920610000111
    Figure BDA0004367920610000111
  • Figure BDA0004367920610000121
    Figure BDA0004367920610000121
Patent Text Reader

Abstract

The invention provides a naphtha reforming catalyst as well as a preparation method and application thereof. The preparation method comprises the following steps: preparing an alumina carrier forming matter containing Sn or containing Sn and Ce; roasting the molded product in an oxygen-free atmosphere to obtain an alumina carrier; the alumina carrier is impregnated with impregnation liquid, the impregnation liquid comprises a Pt-containing compound, a Ce-containing compound and a competitive adsorbent, or the impregnation liquid comprises the Pt-containing compound and the competitive adsorbent; and drying, activating and reducing the impregnated alumina carrier to obtain the naphtha reforming catalyst. The naphtha reforming catalyst provided by the invention is prepared by the preparation method. The invention also provides application of the naphtha reforming catalyst in continuous reforming of naphtha to produce high-octane gasoline blending components or aromatic hydrocarbons. The platinum atoms in the catalyst prepared by the method have strong interaction with the carrier, and the catalyst can meet the high severity reaction process requirements of naphtha catalytic reforming.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a naphtha reforming catalyst and a preparation method and application thereof, in particular to a Pt-Sn-Ce naphtha reforming catalyst and a preparation method and application thereof, belonging to the technical field of reforming catalysts. Background Art

[0002] Catalytic reforming is one of the important production processes in petroleum processing, and its main purpose is to produce high-octane gasoline, BTX aromatics and cheap hydrogen. With the integration of refining and chemical industry, catalytic reforming is becoming more and more important in the refining and chemical industry. At present, the most commonly used reforming catalysts in industry are Pt-Re / Al2O3 catalysts for semi-regenerative reforming process and Pt-Sn / Al2O3 for continuous regenerative reforming process.

[0003] US3915845A discloses a hydrocarbon conversion multimetallic catalyst component, which comprises 0.01-2.0 wt% of Pt group metal, 0.01-5.0 wt% of germanium, 0.1-3.5 wt% of halogen and lanthanide compounds. The lanthanide elements in the catalyst are lanthanum, cerium and neodymium.

[0004] US4039477A discloses a hydroprocessing catalyst modified with lanthanide metals and its application. The catalyst comprises a refractory metal oxide, all members of the Pt family, Sn and at least one metal selected from Y, Th, U, Pr, Ce, La, Nd, Sm, Dy and Gd. The catalyst introduces lanthanide metals to improve the activity and stability of the catalyst, while the presence of tin can reduce the cracking activity of the lanthanide metal-containing catalyst, which is beneficial to improve the selectivity.

[0005] CN1535176A discloses a platinum-tin-containing multi-metal reforming catalyst and its preparation and application. The lanthanide elements introduced into the catalyst are Eu and Ce. The catalyst has high activity and selectivity for naphtha reforming reaction, low carbon deposition rate and long service life.

[0006] CN103596681A discloses a catalytic reforming catalyst for naphtha. The catalyst may have a noble metal comprising one or more of platinum, palladium, rhodium, ruthenium, oxaline and iridium, a lanthanide metal comprising one or more elements of atomic number 57-71 of the periodic table, and a carrier. In the catalyst, the atomic ratio of lanthanide metal: noble metal is less than 1.3:1. Moreover, in the catalyst, the lanthanide metal can be distributed with a lanthanide metal concentration in the surface layer of 100 μm of the catalyst being less than 2 times the lanthanide metal concentration at the central core of the catalyst.

[0007] US20130015103A1 discloses a reforming catalyst, which comprises a noble metal, a lanthanide metal and a carrier, wherein the atomic ratio of the lanthanide metal to the noble metal in the catalyst is less than 1.3:1.

[0008] CN105621464A discloses a method for synthesizing aluminum oxide. In this method, carbon black is mixed with an aluminum salt solution, stirred and ultrasonically treated, and then placed in a nitrogen atmosphere and an oxygen atmosphere in turn to obtain aluminum oxide. CN105600810A discloses a method for preparing a macroporous aluminum oxide material. In this preparation method, carbon black is mixed with an alkali solution and stirred, and then an aluminum salt solution is prepared, and the carbon black obtained by filtration and drying is mixed with the aluminum salt solution, stirred and ultrasonically treated, and then ammonium salt is added, and then the mixture is dried, and finally placed in nitrogen, oxygen, and nitrogen atmospheres in turn to obtain aluminum oxide.

[0009] CN110935458A discloses a method for preparing a hydrodemetallization catalyst. In this preparation method, after the carrier is formed, the formed product is first calcined in a nitrogen atmosphere and then calcined in an oxygen-containing atmosphere to obtain an alumina carrier. When the carrier is calcined in a nitrogen atmosphere, polyols or sugar compounds are carbonized at the rod-shaped alumina clusters. When calcined in an oxygen-containing atmosphere, the formed carbon is rapidly oxidized and combusted and releases heat, so that the temperature around the rod-shaped alumina clusters rises rapidly and is higher than the calcination temperature, so that the alumina grains around the rod-shaped alumina clusters grow further, thereby increasing the content of macropores in the carrier.

[0010] CN108686713A discloses an alumina carrier and a preparation method thereof, a dehydrogenation catalyst and an application thereof. The preparation method of the alumina carrier comprises the following steps: (1) contacting pseudo-boehmite with low-carbon alcohol and performing solid-liquid separation; (2) drying and roasting the solid product obtained by solid-liquid separation under an inert atmosphere to obtain the alumina carrier. The advantage of this technical solution is that the alumina carrier with a large specific surface area, a large pore volume and a uniform pore size distribution can be obtained by the preparation method, which is more conducive to the dispersion of active metal components.

[0011] With the transformation and upgrading of the refining business, many reforming units that produce gasoline have transformed to mainly produce aromatics. For reforming units that produce aromatics, they are usually operated under high severity (high reaction temperature, low hydrogen-to-oil ratio). High severity operating conditions aggravate the aggregation of platinum atoms in the catalyst, which will cause the product selectivity to deteriorate and affect the service life of the catalyst. Therefore, high severity operating conditions put forward higher requirements on the performance of the reforming catalyst. The development of a new type of naphtha reforming catalyst and its preparation method to meet the high severity reaction process requirements of naphtha catalytic reforming has become one of the problems to be solved in this field. Summary of the invention

[0012] In order to solve the above technical problems, the purpose of the present invention is to provide a naphtha reforming catalyst and its preparation method and application. The platinum atoms in the naphtha reforming catalyst prepared by the preparation method of the present invention have a strong interaction with the carrier, which can meet the high-severity reaction process requirements of naphtha catalytic reforming.

[0013] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a naphtha reforming catalyst, which comprises the following steps:

[0014] (1) preparing an alumina support shaped article containing Sn or containing two metals Sn and Ce;

[0015] (2) calcining the molded product obtained in step (1) in an atmosphere free of oxygen to obtain an alumina carrier;

[0016] (3) impregnating the alumina support obtained in step (2) with an impregnation solution, wherein the impregnation solution includes a Pt-containing compound, a Ce-containing compound and a competitive adsorbent, or the impregnation solution includes a Pt-containing compound and a competitive adsorbent, to obtain an impregnated alumina support;

[0017] (4) drying, activating and reducing the impregnated alumina carrier obtained in step (3) to obtain the naphtha reforming catalyst;

[0018] Wherein, based on 100% of the total mass of dry-basis aluminum oxide, the naphtha reforming catalyst comprises 0.01-1% by mass of Pt, 0.01-1% by mass of Sn, 0.01-1% by mass of Ce and 0.3-3.0% by mass of Cl.

[0019] In the above preparation method, preferably, in step (1), the alumina support shaped object containing Sn or containing two metals Sn and Ce is spherical.

[0020] In some specific embodiments of the present invention, the alumina carrier spherical molding containing Sn or Sn and Ce can be prepared by methods familiar in the art, such as: rolling ball method, oil-ammonia column method, hot oil column method or microfluidization forming.

[0021] The present invention does not particularly limit the steps for preparing the alumina support molding containing Sn or containing two metals Sn and Ce, as long as it can meet the requirements of the present invention. In some specific embodiments of the present invention, a spherical alumina support can be prepared first, and then the Sn element or the Sn element and the Ce element can be introduced by an impregnation method. The Sn element or the Sn element and the Ce element can also be introduced during the preparation of the spherical alumina support, such as when rolling a ball or preparing a drop ball colloid. Preferably, the alumina support molding containing Sn or containing two metals Sn and Ce is prepared by introducing the Sn element or the Sn element and the Ce element into the drop ball colloid.

[0022] In the above-mentioned preparation method, preferably, in step (1), the Sn element is introduced into the alumina support molding by a Sn-containing compound, and the Sn-containing compound includes one or a combination of stannous bromide, stannous chloride and tin tetrachloride. In some specific embodiments of the present invention, the Sn-containing compound can be introduced by co-gelation or co-precipitation during the preparation of the alumina support molding. It can be understood by those skilled in the art that the introduction of the Sn element into the drop ball colloid is the introduction of the Sn element by co-gelation or co-precipitation.

[0023] In the above-mentioned preparation method, preferably, in step (1), when preparing an alumina support molding containing two metals Sn and Ce, the Ce element is introduced into the alumina support molding through a Ce-containing compound, and the Ce-containing compound includes one or a combination of cerium sulfate, cerium nitrate, cerium chloride, ammonium cerium nitrate and cerium oxalate; more preferably, the Ce-containing compound includes cerium nitrate and / or cerium chloride. In some specific embodiments of the present invention, the Ce-containing compound can be introduced in the process of preparing the alumina support molding by co-gelation or co-precipitation. It can be understood by those skilled in the art that the introduction of the Ce element into the drop ball colloid is the introduction of the Ce element by co-gelation or co-precipitation.

[0024] In some specific embodiments of the present invention, the Sn-containing compound and the Ce-containing compound are introduced into the alumina support molding in the form of solutions. The present invention does not specifically limit the concentration of these solutions, which can be routinely adjusted by those skilled in the art based on the element content in the catalyst defined by the present invention.

[0025] In the above preparation method, preferably, at least one of the alumina carrier and the impregnation solution contains the rare earth element Ce.

[0026] In the above preparation method, preferably, in step (2), the oxygen-free atmosphere comprises hydrogen, a hydrogen-nitrogen mixture, nitrogen, carbon monoxide or a carbon monoxide-nitrogen mixture. More preferably, the oxygen-free atmosphere comprises a hydrogen-nitrogen mixture, and the volume fraction of hydrogen in the hydrogen-nitrogen mixture is 5 to 95% by volume, more preferably 10 to 70% by volume, and most preferably 15 to 50% by volume.

[0027] In the above preparation method, preferably, in step (2), the atmosphere not containing oxygen is a flowing atmosphere not containing oxygen.

[0028] In the above preparation method, preferably, in step (2), the calcination temperature is 300-1100°C, more preferably 400-850°C, and further preferably 450-700°C.

[0029] In the above preparation method, preferably, in step (2), the calcination time is 0.5 to 8 hours, more preferably 2 to 6 hours.

[0030] In the above preparation method, preferably, step (2) further comprises: after the calcination is completed, cooling the calcined product to room temperature in a flowing atmosphere, and the cooling atmosphere is the same as the calcination atmosphere.

[0031] In the above preparation method, preferably, the alumina carrier obtained in step (2) is spherical, and its diameter is 1 to 3 mm, more preferably 1.4 to 2.0 mm.

[0032] In the above-mentioned preparation method, preferably, in step (3), the impregnation method may be saturated impregnation or supersaturated impregnation under vacuum or non-vacuum state; more preferably, the impregnation method is saturated impregnation or supersaturated impregnation under vacuum state.

[0033] In the above preparation method, preferably, in step (3), the liquid-to-solid volume ratio of the impregnation solution to the alumina support is 0.5-3.

[0034] In some specific embodiments of the present invention, the impregnation process may be static or dynamic. The dynamic process refers to rotating the impregnation container during the impregnation process, and dynamic impregnation is preferred.

[0035] In the above preparation method, preferably, in step (3), the immersion temperature is 20 to 60° C. and the immersion time is 0.1 to 6 hours.

[0036] In the above preparation method, preferably, in step (3), the Pt-containing compound includes one or a combination of chloroplatinic acid, ammonium chloroplatinate, bromoplatinic acid, platinum trichloride, tetraammine platinum nitrate, dichlorocarbonyl platinum dichloride and dinitrodiamino platinum, etc. The Pt-containing compound can be introduced into the alumina support by co-impregnation or step-by-step impregnation.

[0037] In the above preparation method, preferably, in step (3), the Ce-containing compound includes one or a combination of cerium sulfate, cerium nitrate, cerium chloride, ammonium cerium nitrate and cerium oxalate, etc.; more preferably, the Ce-containing compound includes cerium nitrate and / or cerium chloride. The Ce-containing compound can be introduced into the alumina support by co-impregnation or step-by-step impregnation.

[0038] In the above preparation method, preferably, in step (3), the competitive adsorbent includes one or a combination of citric acid, hydrochloric acid, nitric acid, monochloroacetic acid, dichloroacetic acid and trichloroacetic acid, etc.; more preferably, the competitive adsorbent includes hydrochloric acid and / or trichloroacetic acid. The present invention uses a competitive adsorbent during the impregnation process, which can further make the active component metal evenly distributed on the carrier.

[0039] In the above preparation method, preferably, part or all of the chlorine in the naphtha reforming catalyst comes from the competitive adsorbent. The chlorine in the naphtha reforming catalyst can also come from the above Sn-containing compound, Ce-containing compound, and Pt-containing compound. The role of chlorine in the catalyst of the present invention includes adjusting the amount of catalyst acid.

[0040] In step (4) of the above preparation method, the drying temperature and time can be conventionally adjusted by those skilled in the art, and the present invention does not specifically limit them.

[0041] In the above preparation method, preferably, in step (4), the activation atmosphere is air, the activation temperature is 200-650°C, more preferably 450-550°C, and the activation time is 0.5-12 hours, more preferably 1-4 hours.

[0042] In the above preparation method, preferably, in step (4), during the activation process, water and chlorine gas or chlorine-containing organic matter are injected, and the molar ratio of water to chlorine element is (10-120):1. More preferably, the chlorine-containing organic matter includes one or a combination of chlorinated hydrocarbons such as ethylene dichloride, carbon tetrachloride and tetrachloroethylene. The chlorine in the naphtha reforming catalyst can also come from the chlorine gas or chlorine-containing organic matter injected during the activation process.

[0043] It can be understood by those skilled in the art that, since the present invention can introduce a Pt-containing compound or a Pt-containing compound and a Ce-containing compound into the alumina carrier by co-impregnation or step-by-step impregnation, the impregnation solution described in the present invention can be an impregnation solution containing a Pt-containing compound, or an impregnation solution containing a Pt-containing compound and an impregnation solution containing a Ce-containing compound, or an impregnation solution containing a Pt-containing compound and a Ce-containing compound. The present invention does not specifically limit the concentration of the compound in the impregnation solution, and it can be conventionally adjusted by those skilled in the art according to the element content in the catalyst defined by the present invention. In addition, when the step-by-step impregnation method is adopted, the metal-loaded carrier can be dried and activated after each impregnation step.

[0044] In the above preparation method, in step (4), the reducing atmosphere may be hydrogen, or other reducing gases such as CO. Preferably, the reducing atmosphere is hydrogen.

[0045] In the above preparation method, preferably, in step (4), the reduction temperature is 200 to 650° C., more preferably 400 to 580° C., and the reduction time is 0.5 to 8 hours, more preferably 1 to 4 hours.

[0046] In the above preparation method, preferably, based on the total mass of dry aluminum oxide as 100%, the content of Pt (in terms of element amount) in the naphtha reforming catalyst is 0.01-0.6 mass%, more preferably 0.1-0.4 mass%, and further preferably 0.1-0.3 mass%.

[0047] In the above preparation method, preferably, based on 100% of the total mass of dry aluminum oxide, the content of Sn (calculated as the amount of the element) in the naphtha reforming catalyst is 0.1-0.6% by mass, more preferably 0.1-0.5% by mass.

[0048] In the above preparation method, preferably, based on 100% of the total mass of dry-basis aluminum oxide, the content of Ce (calculated as the amount of the element) in the naphtha reforming catalyst is 0.1 to 0.6% by mass.

[0049] In the above preparation method, preferably, based on 100% of the total mass of dry aluminum oxide, the content of Cl (in terms of element) in the naphtha reforming catalyst is 0.6 to 2.0% by mass, more preferably 0.9 to 1.5% by mass.

[0050] In the above-mentioned preparation method, the Pt in the naphtha reforming catalyst may exist in the form of a metal or a compound, such as an oxide, a sulfide, a halide (such as a chloride), an oxyhalide (such as an oxychloride), etc., or may exist in a physical or chemical combination with other components in the carrier and the catalyst. Preferably, the Pt in the naphtha reforming catalyst exists in the form of a metal. After the reduction step of the present invention, most or even all of the Pt in the catalyst is reduced to a metal state, but a small amount of Pt in other forms may still exist.

[0051] In the above preparation method, the Sn in the naphtha reforming catalyst may exist in the form of metal or compound, such as oxide, sulfide, halide (such as chloride), oxyhalide (such as oxychloride), etc., or may exist in a physical or chemical combination with other components in the carrier and the catalyst. Preferably, the Sn in the naphtha reforming catalyst exists in an oxidized form.

[0052] In the above preparation method, the Ce in the naphtha reforming catalyst may exist in the form of a compound, such as an oxide, a sulfide, a halide (such as a chloride), an oxyhalide (such as an oxychloride), etc., or may exist in a physical or chemical combination with other components in the carrier and the catalyst. Preferably, the Ce in the naphtha reforming catalyst exists in an oxidized state, and the valence state of Ce is +3 and / or +4.

[0053] In the above-mentioned preparation method, preferably, the crystalline form of alumina in the naphtha reforming catalyst includes one or a combination of γ-Al2O3, η-Al2O3 and θ-Al2O3; more preferably, the crystalline form of alumina in the naphtha reforming catalyst is γ-Al2O3 or η-Al2O3, and further preferably is γ-Al2O3.

[0054] A second aspect of the present invention provides a naphtha reforming catalyst, which is prepared by the above-mentioned naphtha reforming catalyst preparation method; based on the total mass of dry basis alumina as 100%, the naphtha reforming catalyst includes 0.01 to 1 mass% of Pt, 0.01 to 1 mass% of Sn, 0.01 to 1 mass% of Ce and 0.3 to 3.0 mass% of Cl.

[0055] According to a specific embodiment of the present invention, preferably, based on the total mass of dry-basis alumina as 100%, the content of Pt (in terms of the amount of the element) in the naphtha reforming catalyst is 0.01 to 0.6 mass %, more preferably 0.1 to 0.4 mass %, and further preferably 0.1 to 0.3 mass %.

[0056] According to a specific embodiment of the present invention, preferably, based on 100% of the total mass of dry-basis alumina, the content of Sn (calculated as the amount of the element) in the naphtha reforming catalyst is 0.1-0.6% by mass, more preferably 0.1-0.5% by mass.

[0057] According to a specific embodiment of the present invention, preferably, based on 100% of the total mass of dry-basis aluminum oxide, the content of Ce (calculated as the amount of the element) in the naphtha reforming catalyst is 0.1 to 0.6% by mass.

[0058] According to a specific embodiment of the present invention, preferably, based on 100% of the total mass of dry-basis aluminum oxide, the content of Cl (calculated as the amount of the element) in the naphtha reforming catalyst is 0.6-2.0% by mass, more preferably 0.9-1.5% by mass.

[0059] According to a specific embodiment of the present invention, preferably, the Pt in the naphtha reforming catalyst exists in a metallic form.

[0060] According to a specific embodiment of the present invention, preferably, Sn in the naphtha reforming catalyst exists in an oxidized form.

[0061] According to a specific embodiment of the present invention, preferably, Ce in the naphtha reforming catalyst exists in an oxidized form, and the valence state of Ce is +3 and / or +4.

[0062] According to a specific embodiment of the present invention, preferably, the crystalline form of alumina in the naphtha reforming catalyst includes one or a combination of γ-Al2O3, η-Al2O3 and θ-Al2O3; more preferably, the crystalline form of alumina in the naphtha reforming catalyst is γ-Al2O3 or η-Al2O3, and further preferably is γ-Al2O3.

[0063] According to a specific embodiment of the present invention, preferably, the dispersion degree of Pt in the naphtha reforming catalyst is 96-100%.

[0064] According to a specific embodiment of the present invention, preferably, the Pt dispersion of the aged catalyst obtained after the naphtha reforming catalyst is treated in a hydrogen atmosphere at 700° C. for 12 hours is greater than 80%.

[0065] Generally speaking, the dispersion of Pt can be calculated by the following formula:

[0066]

[0067] Where D is the dispersion of Pt.

[0068] A third aspect of the present invention provides a use of the above naphtha reforming catalyst in the continuous reforming of naphtha to produce high-octane gasoline blending components or aromatics.

[0069] In the above application, preferably, the naphtha used includes one or a combination of straight-run gasoline, hydrocracked heavy naphtha, thermally cracked or catalytically cracked gasoline fractions, and Fischer-Tropsch gasoline.

[0070] In the above application, preferably, the naphtha used includes full boiling range gasoline with an initial boiling point of 40-80°C and a final boiling point of 160-220°C as measured by the method of ASTM D-86, and / or naphtha with a distillation range of 60-150°C, and / or heavy naphtha with a distillation range of 100-200°C. The reforming raw material naphtha preferably used in the present invention is rich in cycloalkanes and paraffins.

[0071] In the above application, preferably, the reaction conditions of naphtha continuous reforming include: absolute pressure of 100 KPa to 7 MPa, more preferably 0.35 to 2.5 MPa; reaction temperature of 315 to 600° C., more preferably 425 to 565° C.; hydrogen / hydrocarbon molar ratio of 1 to 10, more preferably 2 to 5; liquid hourly space velocity (LHSV) of 0.1 to 10 hours -1 , more preferably 1 to 5 hours -1 .

[0072] In the above application, preferably, the process of continuous reforming of naphtha is carried out under substantially anhydrous conditions. More preferably, the water content of the reforming feedstock when entering the reforming reactor should be less than 50 ppm, preferably less than 20 ppm. The reforming feedstock can be dried by conventional adsorbents to remove water therein, and the adsorbent can be a molecular sieve, etc.; it can also be dried by appropriate stripping operation by conventional fractionation equipment to remove water therein; it can also be combined with adsorption drying and stripping drying to remove water from the reforming feedstock.

[0073] The present invention provides a Pt-Sn-Ce naphtha reforming catalyst and a preparation method and application thereof. The technical solution of the present invention has at least the following beneficial technical effects:

[0074] In the process of preparing the catalyst, the aluminum oxide carrier molded product containing Sn or containing two metals Sn and Ce is roasted in an atmosphere without oxygen, so that the prepared aluminum oxide carrier contains more defect sites, and these defect sites have a strong anchoring effect on Pt atoms. In the process of high-temperature reaction of naphtha catalytic reforming and high-temperature charring of the catalyst, since the Pt atoms in the catalyst of the present invention have a strong interaction with the carrier, the Pt atoms are not easy to aggregate. Therefore, the naphtha reforming catalyst of the present invention has good selectivity, high liquid yield, less dry gas and coke generated, and good stability of the catalyst, long service life, and can meet the high-rigidity reaction process requirements of naphtha catalytic reforming. DETAILED DESCRIPTION

[0075] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0076] Preparation Examples 1 to 5

[0077] Preparation Examples 1 to 5 respectively provide an alumina carrier, which is prepared by the following steps:

[0078] 1000 g of pseudo-boehmite (produced by Sasol) and an appropriate amount of deionized water were mixed in a liquid / solid mass ratio of 2, and the mixture was stirred at room temperature to form a slurry for 0.5 hour; then 30 ml of nitric acid and a predetermined amount of stannous chloride hydrochloric acid solution were added to make the Sn content in the solution 0.30% by mass relative to the dry basis alumina, and the mixture was acidified for 2 hours to obtain a mixture; then the mixture was dripped into an oil-ammonia column to form a ball, and the obtained wet ball was solidified in ammonia water for 1 hour, then filtered, washed three times with deionized water, dried at 60° C. for 6 hours, and then dried at 120° C. for 2 hours to obtain a Sn-containing alumina carrier molding;

[0079] 200 g of Sn-containing alumina carrier molded product was taken and placed in a quartz reactor, and the air was first replaced with nitrogen, and then the temperature was raised to 650°C in a flowing atmosphere without oxygen and constant temperature roasted for 4 hours, and then the temperature was lowered to room temperature in the flowing atmosphere to obtain Sn-containing alumina carriers S1 to S5. Carriers S1 to S5 are all small balls with a diameter of 1.6±0.2 mm.

[0080] The Sn content, calcination atmosphere, calcination conditions and cooling atmosphere of carriers S1 to S5 are shown in Table 1.

[0081] Preparation Example 6

[0082] This preparation example provides an alumina carrier, and its preparation steps are basically the same as those of Preparation Example 3, except that: the Sn content in the Sn-containing alumina carrier is 0.47 mass % relative to the dry basis alumina, and the calcination condition is calcination at 450° C. in a flowing atmosphere for 6 hours to obtain the Sn-containing alumina carrier S6. The carrier S6 is a small ball with a diameter of 1.6±0.2 mm.

[0083] The Sn content, calcination atmosphere, calcination conditions and cooling atmosphere of carrier S6 are shown in Table 1.

[0084] Preparation Example 7

[0085] This preparation example provides an alumina carrier, which is prepared by the following steps:

[0086] 1000 g of pseudo-boehmite (produced by Sasol) and an appropriate amount of deionized water were mixed in a liquid / solid mass ratio of 2, and the mixture was stirred at room temperature to form a slurry for 0.5 hour; then 30 ml of nitric acid and a predetermined amount of stannous chloride and cerium chloride hydrochloric acid solution were added so that the Sn content and Ce content in the solution were 0.10% by mass and 0.20% by mass relative to the dry basis alumina, respectively, and the mixture was acidified for 2 hours to obtain a mixture; then the mixture was dripped into an oil-ammonia column to form a ball, and the obtained wet ball was solidified in ammonia water for 1 hour, then filtered, washed three times with deionized water, dried at 60° C. for 6 hours, and then dried at 120° C. for 2 hours to obtain an alumina carrier molded product containing Sn and Ce;

[0087] 200 g of Sn and Ce-containing alumina carrier molded product was taken and placed in a quartz reactor, the air was first replaced with nitrogen, then the temperature was raised to 800° C. in a flowing 30% volume H2-70% volume N2 mixed atmosphere and constant temperature calcined for 2 hours, and the temperature was lowered to room temperature in a flowing hydrogen-nitrogen mixed atmosphere to obtain Sn and Ce-containing alumina carrier S7. Carrier S7 is a small ball with a diameter of 1.6±0.2 mm.

[0088] The Sn content, Ce content, calcination atmosphere, calcination conditions and cooling atmosphere of carrier S7 are shown in Table 1.

[0089] Preparation Example 8

[0090] This preparation example provides an alumina carrier, and its preparation steps are basically the same as those of Preparation Example 1, except that: 200 g of Sn-containing alumina carrier molding is taken, placed in a quartz reactor, heated to 650° C. in a flowing air atmosphere and calcined at a constant temperature for 4 hours, and then cooled to room temperature in a flowing air atmosphere to obtain Sn-containing alumina carrier S8. Carrier S8 is a small ball with a diameter of 1.6±0.2 mm.

[0091] The Sn content, calcination atmosphere, calcination conditions and cooling atmosphere of carrier S8 are shown in Table 1.

[0092] Preparation Example 9

[0093] This preparation example provides an alumina carrier, and its preparation steps are basically the same as those of Preparation Example 1, except that: 200 grams of Sn-containing alumina carrier molding is taken and placed in a quartz reactor, and the air is first replaced with nitrogen, and then the temperature is raised to 650°C in a flowing 80% volume H2-20% volume N2 mixed atmosphere and constant temperature roasted for 4 hours, and nitrogen and air replacement are performed at 650°C, and then the temperature is cooled to room temperature in a flowing air atmosphere to obtain Sn-containing alumina carrier S9. Carrier S9 is a small ball with a diameter of 1.6±0.2 mm.

[0094] The Sn content, calcination atmosphere, calcination conditions and cooling atmosphere of carrier S9 are shown in Table 1.

[0095] Preparation Example 10

[0096] This preparation example provides an alumina carrier, and its preparation steps are basically the same as those of Preparation Example 7, except that: after calcination in a hydrogen-nitrogen mixed atmosphere, it is switched to 100 volume % nitrogen, and then cooled to room temperature in a flowing nitrogen atmosphere to obtain an alumina carrier S10 containing Sn and Ce. The carrier S10 is a small sphere with a diameter of 1.6±0.2 mm.

[0097] The Sn content, Ce content, calcination atmosphere, calcination conditions and cooling atmosphere of the carrier S10 are shown in Table 1.

[0098] Preparation Example 11

[0099] This preparation example provides an alumina carrier, and its preparation steps are basically the same as those of Preparation Example 1, except that: the Sn content in the Sn-containing alumina carrier is 0.1% by mass relative to the dry basis alumina, 200 grams of the Sn-containing alumina carrier molded product is taken and placed in a quartz reactor, the air is first replaced with nitrogen, and then the temperature is raised to 650°C in a flowing carbon monoxide atmosphere and constant-temperature roasted for 4 hours, and then the temperature is lowered to room temperature in a flowing carbon monoxide atmosphere to obtain the Sn-containing alumina carrier S11. The carrier S11 is a small ball with a diameter of 1.6±0.2 mm.

[0100] The Sn content, calcination atmosphere, calcination conditions and cooling atmosphere of carrier S11 are shown in Table 1.

[0101] Test Example 1

[0102] This test example tests the specific surface area, pore volume, pore diameter and alumina crystal phase of the carriers S1 to S11 provided in Preparation Examples 1 to 11.

[0103] The structural properties of carriers S1-S11 were measured at -196°C using an ASAP 2020 analyzer produced by Micromeritics, USA. Before the measurement, the samples of carriers S1-S11 were degassed at 300°C for 4 hours. The specific surface area and pore structure data of carriers S1-S11 were obtained from the adsorption and desorption isotherms using the Brunauer-Emmett-Teller (BET) method and the Barrett-Joyner-Halenda (BJH) method.

[0104] The alumina crystal phase of carriers S1 to S11 was analyzed using a Bruker-D8 XRD analyzer with a Cu target as the light source and Kα (λ=0.154 nm) radiation. Data were collected at 40 kV and 40 mA in the range of 5-80° (2θ) with a step size of 0.02°.

[0105] The test results are shown in Table 1.

[0106] Table 1

[0107]

[0108]

[0109] It can be seen from Table 1 that the specific surface area, pore volume and pore diameter of the carrier prepared by calcining in an atmosphere without oxygen are slightly smaller than those of the carrier prepared by calcining in an atmosphere containing oxygen, but the overall difference is not significant. The main factor affecting the specific surface area, pore volume and pore diameter of the carrier is the calcination temperature.

[0110] Example 1

[0111] This embodiment provides a naphtha reforming catalyst, which is prepared by the following steps:

[0112] 100 g of carrier S1 is taken, and an impregnation solution containing chloroplatinic acid, trichloroacetic acid, hydrochloric acid and cerium chloride is prepared according to a predetermined amount, wherein the mass contents of platinum, trichloroacetic acid, hydrochloric acid and cerium in the impregnation solution are 0.3%, 5%, 1.2% and 0.1% respectively relative to the mass of dry aluminum oxide; the impregnation solution is contacted with the carrier S1 at a liquid-to-solid volume ratio of 1.8:1 at 20°C and vacuum state for 6 hours, and then rotary evaporated to dryness, and then dried at 120°C for 12 hours to obtain a catalyst precursor; the catalyst precursor is activated in an air atmosphere at 200°C for 8 hours, and then activated at 480°C for 4 hours, and water and carbon tetrachloride are injected at a H2O:Cl molar ratio of 40:1 during the air activation at 480°C. After the air activation is completed, the activated catalyst precursor is reduced with hydrogen at 480°C for 4 hours to obtain a catalyst A.

[0113] The contents of Pt, Sn, Ce and Cl in Catalyst A are shown in Table 2. The contents of Pt, Sn, Ce and Cl in Table 2 are all based on the total mass of dry aluminum oxide as 100%.

[0114] In the embodiments and comparative examples of the present invention, the contents of Pt, Sn and Ce in the catalyst are determined by X-ray fluorescence spectrometry (for the specific determination method, please refer to the literature: Gao Ping, Gu Ruojing. Determination of platinum, europium and cerium in reforming catalyst by X-ray fluorescence spectrometry [J]. Analysis Laboratory, 2002 (06): 80-82.), and the chlorine content in the catalyst is determined according to the standard SH / T 0343-1992 Determination of chlorine content in catalyst (ion selective electrode method).

[0115] Embodiments 2 to 5

[0116] Examples 2 to 5 provide a naphtha reforming catalyst, respectively. Their preparation methods are basically the same as those of Example 1, except that carriers S2, S3, S4 and S5 are used to prepare catalysts B, C, D and E. The contents of Pt, Sn, Ce and Cl in catalysts B, C, D and E are shown in Table 2.

[0117] Example 6

[0118] This embodiment provides a naphtha reforming catalyst, which is prepared by the following steps:

[0119] 100 g of carrier S3 is taken, and a cerium sulfate impregnation solution is prepared according to a predetermined amount, wherein the mass content of cerium in the impregnation solution is 0.3% relative to the mass of dry aluminum oxide; the cerium chloride impregnation solution is sprayed on the carrier S3 by a saturated impregnation method, and then dried at 120° C. for 6 hours, and then activated at 550° C. for 4 hours in an air atmosphere to obtain the Ce-loaded carrier S3; an impregnation solution containing chloroplatinic acid, trichloroacetic acid, and hydrochloric acid is prepared according to a predetermined amount, and the mass contents of platinum, trichloroacetic acid, and hydrochloric acid in the impregnation solution are 0.3%, 5%, and 1.2% relative to the mass of dry aluminum oxide, respectively. ; The impregnation liquid is contacted with the Ce-loaded carrier S3 at a liquid-to-solid volume ratio of 1.8:1 at 20°C and vacuum state for 6 hours, then rotary evaporated to dryness, and then dried at 120°C for 12 hours to obtain a catalyst precursor; the catalyst precursor is activated in an air atmosphere at 200°C for 8 hours, then activated at 480°C for 4 hours, and water and tetrachloroethylene are injected during the air activation at 480°C at a molar ratio of H2O:Cl of 10:1. After the air activation is completed, the activated catalyst precursor is reduced with hydrogen at 480°C for 4 hours to obtain a catalyst F.

[0120] The contents of Pt, Sn, Ce and Cl in Catalyst F are shown in Table 2.

[0121] Example 7

[0122] This embodiment provides a naphtha reforming catalyst, which is prepared by the following steps:

[0123] Take 100g of carrier S5, prepare an impregnation solution containing chloroplatinic acid, hydrochloric acid and cerium nitrate according to predetermined amounts, the mass contents of platinum, hydrochloric acid and cerium in the impregnation solution being 0.2%, 3% and 0.4% respectively relative to the mass of dry basis alumina; make the impregnation solution contact with carrier S5 at a liquid-to-solid volume ratio of 1.8:1 at 20°C and vacuum state for 6 hours, then rotary evaporate to dryness, and then dry at 120°C for 12 hours to obtain a catalyst precursor; activate the catalyst precursor in a flowing air atmosphere at 560°C for 4 hours, inject water and dichloroethane at a H2O:Cl molar ratio of 80:1 during the air activation at 560°C, and after the air activation is completed, reduce the activated catalyst precursor with hydrogen at 600°C for 0.5 hour to obtain catalyst G.

[0124] The contents of Pt, Sn, Ce and Cl in Catalyst G are shown in Table 2.

[0125] Example 8

[0126] This embodiment provides a naphtha reforming catalyst, which is prepared by the following steps:

[0127] Take 100g of carrier S6, prepare an impregnation solution containing chloroplatinic acid, hydrochloric acid and cerium oxalate according to a predetermined amount, the mass contents of platinum, hydrochloric acid and cerium in the impregnation solution are 0.2%, 2% and 0.4% respectively relative to the mass of dry aluminum oxide; make the impregnation solution and carrier S6 contact at a liquid-to-solid volume ratio of 1.8:1 at 20°C and vacuum state for 6 hours, then rotary evaporate to dryness, and then dry at 120°C for 12 hours to obtain a catalyst precursor; activate the catalyst precursor in a flowing air atmosphere at 510°C for 4 hours, inject water and tetrachloroethylene at a molar ratio of H2O:Cl of 30:1 during the air activation at 510°C, and after the air activation is completed, reduce the activated catalyst precursor with hydrogen at 500°C for 2 hours to obtain catalyst H.

[0128] The contents of Pt, Sn, Ce and Cl in Catalyst H are shown in Table 2.

[0129] Example 9

[0130] This embodiment provides a naphtha reforming catalyst, which is prepared by the following steps:

[0131] 100 g of carrier S7 is taken, and a cerium nitrate impregnation solution is prepared according to a predetermined amount, wherein the mass content of cerium in the impregnation solution is 0.4% relative to the mass of dry aluminum oxide; the cerium nitrate impregnation solution is sprayed on the carrier S7 by a saturated impregnation method, and then dried at 120° C. for 6 hours, and then activated in an air atmosphere at 600° C. for 4 hours to obtain a Ce-loaded carrier S7; an impregnation solution containing chloroplatinic acid and hydrochloric acid is prepared according to a predetermined amount, and the mass contents of platinum and hydrochloric acid in the impregnation solution are 0.1% and 1.2% respectively relative to the mass of dry aluminum oxide. The impregnation liquid was brought into contact with the Ce-loaded carrier S7 at a liquid-to-solid volume ratio of 1.8:1 at 20°C under vacuum for 6 hours, and then rotary evaporated to dryness, and then dried at 120°C for 12 hours to obtain a catalyst precursor; the catalyst precursor was activated in a flowing air atmosphere at 450°C for 6 hours, and water and tetrachloroethylene were injected at a H2O:Cl molar ratio of 20:1 during the air activation at 450°C. After the air activation, the activated catalyst precursor was reduced with hydrogen at 480°C for 4 hours to obtain Catalyst I.

[0132] The contents of Pt, Sn, Ce and Cl in Catalyst I are shown in Table 2.

[0133] Example 10

[0134] This embodiment provides a naphtha reforming catalyst, which is prepared by the following steps:

[0135] Take 100g of carrier S11, prepare an impregnation solution containing chloroplatinic acid, hydrochloric acid and cerium chloride according to predetermined amounts, the mass contents of platinum, hydrochloric acid and cerium in the impregnation solution being 0.11%, 1.5% and 0.84% ​​respectively relative to the mass of dry basis alumina; make the impregnation solution contact with the carrier S11 at a liquid-to-solid volume ratio of 1.8:1 at 20°C and vacuum state for 6 hours, then rotary evaporate to dryness, and then dry at 120°C for 12 hours to obtain a catalyst precursor; activate the catalyst precursor in a flowing air atmosphere at 510°C for 4 hours, inject water and tetrachloroethylene at a H2O:Cl molar ratio of 80:1 during the air activation at 510°C, and after the air activation is completed, reduce the activated catalyst precursor with hydrogen at 500°C for 2 hours to obtain catalyst J.

[0136] The contents of Pt, Sn, Ce and Cl in Catalyst J are shown in Table 2.

[0137] Comparative Example 1

[0138] This comparative example provides a naphtha reforming catalyst, which is prepared by the following steps: 100 g of carrier S8 is taken, and catalyst R is prepared according to the steps in Example 1.

[0139] The contents of Pt, Sn, Ce and Cl in Catalyst R are shown in Table 2.

[0140] Comparative Example 2

[0141] This comparative example provides a naphtha reforming catalyst, which is prepared by the following steps: 100 g of carrier S9 is taken, and catalyst S is prepared according to the steps in Example 6.

[0142] The contents of Pt, Sn, Ce and Cl in Catalyst S are shown in Table 2.

[0143] Comparative Example 3

[0144] This comparative example provides a naphtha reforming catalyst, which is prepared by the following steps: 100 g of carrier S10 is taken, and catalyst T is prepared according to the steps in Example 9.

[0145] The contents of Pt, Sn, Ce and Cl in Catalyst T are shown in Table 2.

[0146] Table 2

[0147] catalyst Carrier Pt (mass %) Sn (mass%) Ce (mass %) Cl (mass%) Example 1 A S1 0.29 0.31 0.10 1.23 Example 2 B S2 0.30 0.30 0.09 1.21 Example 3 C S3 0.30 0.29 0.11 1.24 Example 4 D S4 0.29 0.30 0.09 1.20 Example 5 E S5 0.30 0.30 0.11 1.18 Example 6 F S3 0.29 0.30 0.29 1.43 Example 7 G S5 0.20 0.30 0.38 1.06 Example 8 H S6 0.19 0.46 0.39 1.17 Example 9 I S7 0.10 0.11 0.61 0.99 Example 10 J S11 0.11 0.10 0.83 1.05 Comparative Example 1 R S8 0.30 0.29 0.10 1.20 Comparative Example 2 S S9 0.29 0.29 0.30 1.41 Comparative Example 3 T S10 0.11 0.10 0.60 1.01

[0148] Test Example 2

[0149] This test case tests the platinum dispersion of fresh catalyst and aged catalyst.

[0150] The aging treatment of the catalyst is carried out according to the following method: 10 grams of fresh catalyst (i.e., reduced catalysts A to J and R to T provided in the examples and comparative examples) are placed in a reactor and treated in a hydrogen atmosphere at 700° C. for 12 hours to obtain an aged catalyst.

[0151] This test example was carried out according to the following method: 0.5 g of fresh catalyst or aged catalyst of 20-40 mesh was taken and loaded into a U-tube, and the temperature was increased to 500°C at a rate of 15°C / min in an Ar-H2 gas flow containing 5 volume % H2 at a flow rate of 30 ml / min for supplementary reduction for 1 hour, and then the temperature was lowered to the program set temperature; the pipeline and the U-tube were purged with 30 ml / min of He gas for 45 minutes, and a He-O2 gas flow containing 5 volume % O2 at 30 ml / min was used as the loop gas for oxygen titration; then the pipeline and the U-tube were purged with 30 ml / min of Ar gas for 45 minutes, and a hydrogen titration was carried out using a 30 ml / min of Ar gas containing 5 volume % H2 as the loop gas.

[0152] The platinum dispersion was calculated according to the following formula:

[0153]

[0154] Where D is the Pt dispersion; V H is the total volume of the sample under standard conditions of H2 consumption, ml; 22414 is the standard volume of gas, ml / mol; M Pt is the relative atomic mass of Pt, i.e. 195 g / mol; W is the mass of the catalyst sample, g; P is the mass fraction of Pt in the catalyst, %.

[0155] The platinum dispersion of the fresh catalyst and the aged catalyst is shown in Table 3.

[0156] Table 3

[0157]

[0158] It can be seen from the platinum dispersion data in Table 3 that, for fresh catalysts, there is little difference between the catalysts of the embodiments of the present invention and the catalysts of the comparative examples; however, after the catalysts are aged at high temperatures, the degree of platinum aggregation in the catalysts of the comparative examples increases, while the platinum metal in the catalysts of the embodiments of the present invention has better thermal stability at high temperatures.

[0159] Test Example 3

[0160] This test example examines the reaction performance of the aged catalyst.

[0161] In a 100mL device, 50mL of aged catalyst (the aging method of the catalyst is the same as that of Test Example 2) was loaded, and straight-run naphtha with a distillation range of 80-172°C was used as the feed oil. The properties of the feed oil are shown in Table 4. The catalyst evaluation conditions are: reaction pressure of 0.69MPa, reaction temperature of 505°C, liquid feed volume space velocity of 2h -1 , the hydrogen / hydrocarbon molar ratio was 3.5, and the evaluation results are shown in Table 5. The carbon deposition on the catalyst was measured by a CS-744 sulfur-carbon analyzer produced by LECO.

[0162] Table 4 Raw oil properties

[0163]

[0164] Table 5 Evaluation results of aged catalyst

[0165] catalyst <![CDATA[C5 + Yield, m%]]> Aromatic yield, m% Catalyst carbon deposition, m% A 85.0 63.9 3.36 C 85.7 65.3 2.67 D 84.8 63.7 3.41 E 84.0 62.9 3.86 G 83.7 62.5 3.89 J 85.5 64.9 2.72 B 86.2 65.5 2.14 R 81.1 60.5 5.97 F 86.5 65.0 2.39 S 82.3 61.7 5.73 I 86.8 65.3 2.12 T 84.7 63.3 3.75

[0166] It can be seen from the results in Table 5 that, for the aged catalyst, the catalyst of the embodiment of the present invention has higher liquid yield and aromatics yield and lower coke yield than the catalyst of the comparative example. The catalyst exhibits better activity and stability and can meet the high-rigidity reaction process requirements of naphtha catalytic reforming.

Claims

1. A method for preparing a naphtha reforming catalyst, comprising the following steps: (1) preparing an alumina support shaped article containing Sn or containing two metals Sn and Ce; (2) calcining the molded product obtained in step (1) in an atmosphere free of oxygen to obtain an alumina carrier; (3) impregnating the alumina support obtained in step (2) with an impregnation solution, wherein the impregnation solution includes a Pt-containing compound, a Ce-containing compound and a competitive adsorbent, or the impregnation solution includes a Pt-containing compound and a competitive adsorbent, to obtain an impregnated alumina support; (4) drying, activating and reducing the impregnated alumina carrier obtained in step (3) to obtain the naphtha reforming catalyst; Wherein, based on 100% of the total mass of dry-basis aluminum oxide, the naphtha reforming catalyst comprises 0.01-1% by mass of Pt, 0.01-1% by mass of Sn, 0.01-1% by mass of Ce and 0.3-3.0% by mass of Cl.

2. The preparation method according to claim 1, wherein In step (1), the alumina support shaped object containing Sn or containing two metals Sn and Ce is spherical; Preferably, the alumina support shaped article containing Sn or containing two metals Sn and Ce is prepared by introducing Sn element or Sn element and Ce element into a drop ball colloid.

3. The preparation method according to claim 1 or 2, wherein In step (1), the Sn element is introduced into the alumina support molding via a Sn-containing compound, wherein the Sn-containing compound comprises one or a combination of stannous bromide, stannous chloride and tin tetrachloride.

4. The preparation method according to claim 1 or 2, wherein: In step (1), when preparing an alumina support shaped article containing two metals, Sn and Ce, the Ce element is introduced into the alumina support shaped article via a Ce-containing compound, wherein the Ce-containing compound comprises one or a combination of cerium sulfate, cerium nitrate, cerium chloride, ammonium cerium nitrate and cerium oxalate; Preferably, the Ce-containing compound includes cerium nitrate and / or cerium chloride.

5. The preparation method according to claim 1, wherein At least one of the alumina support and the impregnation solution contains the rare earth element Ce.

6. The preparation method according to claim 1, wherein In step (2), the oxygen-free atmosphere includes hydrogen, a hydrogen-nitrogen mixture, nitrogen, carbon monoxide, or a carbon monoxide-nitrogen mixture; Preferably, the oxygen-free atmosphere comprises a hydrogen-nitrogen mixed gas, and the volume fraction of hydrogen in the hydrogen-nitrogen mixed gas is 5 to 95 volume %, more preferably 10 to 70 volume %, and further preferably 15 to 50 volume %; Preferably, in step (2), the oxygen-free atmosphere is a flowing atmosphere that does not contain oxygen; Preferably, in step (2), the calcination temperature is 300 to 1100° C., more preferably 400 to 850° C., and further preferably 450 to 700° C.; Preferably, in step (2), the calcination time is 0.5 to 8 hours, more preferably 2 to 6 hours; Preferably, step (2) further comprises: after the calcination is completed, cooling the calcined product to room temperature in a flowing atmosphere, wherein the cooling atmosphere is the same as the calcination atmosphere.

7. The preparation method according to claim 1, wherein In step (3), the impregnation method is saturated impregnation or supersaturated impregnation under vacuum or non-vacuum state; preferably, the impregnation method is saturated impregnation or supersaturated impregnation under vacuum state; Preferably, in step (3), the liquid-to-solid volume ratio of the impregnation solution to the alumina support is 0.5 to 3; Preferably, in step (3), the immersion temperature is 20 to 60° C. and the immersion time is 0.1 to 6 hours.

8. The preparation method according to claim 1, wherein In step (3), the Pt-containing compound includes one or a combination of chloroplatinic acid, ammonium chloroplatinate, bromoplatinic acid, platinum trichloride, tetraammine platinum nitrate, dichlorocarbonyl platinum dichloride and dinitrodiaminoplatinum.

9. The preparation method according to claim 1, wherein In step (3), the Ce-containing compound includes one or a combination of cerium sulfate, cerium nitrate, cerium chloride, ammonium cerium nitrate and cerium oxalate; Preferably, the Ce-containing compound includes cerium nitrate and / or cerium chloride.

10. The preparation method according to claim 1, wherein: In step (3), the competitive adsorbent includes one or a combination of citric acid, hydrochloric acid, nitric acid, monochloroacetic acid, dichloroacetic acid and trichloroacetic acid; Preferably, the competitive adsorbent comprises hydrochloric acid and / or trichloroacetic acid.

11. The preparation method according to claim 1, wherein: The chlorine in the naphtha reforming catalyst is partially or entirely derived from the competitive adsorbent.

12. The preparation method according to claim 1, wherein: In step (4), the activation atmosphere is air, the activation temperature is 200 to 650° C., and the activation time is 0.5 to 12 hours.

13. The preparation method according to claim 1, wherein In step (4), during the activation process, water and chlorine gas or chlorine-containing organic matter are injected, and the molar ratio of water to chlorine element is (10-120):1; Preferably, the chlorine-containing organic matter includes one or a combination of ethylene dichloride, carbon tetrachloride and tetrachloroethylene.

14. The preparation method according to claim 1, wherein: In step (4), the reducing atmosphere is hydrogen; Preferably, in step (4), the reduction temperature is 200 to 650° C., and the reduction time is 0.5 to 8 hours.

15. A naphtha reforming catalyst, which is prepared by the preparation method of the naphtha reforming catalyst according to any one of claims 1 to 14; based on the total mass of dry-basis alumina as 100%, the naphtha reforming catalyst comprises 0.01 to 1 mass % of Pt, 0.01 to 1 mass % of Sn, 0.01 to 1 mass % of Ce and 0.3 to 3.0 mass % of Cl.

16. The naphtha reforming catalyst according to claim 15, wherein The content of Pt in the naphtha reforming catalyst is 0.01 to 0.6 mass %, preferably 0.1 to 0.4 mass %, based on the total mass of dry aluminum oxide as 100%; Preferably, the content of Sn in the naphtha reforming catalyst is 0.1 to 0.6 mass % based on the total mass of dry-basis alumina as 100%; Preferably, the content of Ce in the naphtha reforming catalyst is 0.1 to 0.6 mass % based on the total mass of dry aluminum oxide as 100%; Preferably, based on 100% of the total mass of dry-basis aluminum oxide, the content of Cl in the naphtha reforming catalyst is 0.6 to 2.0% by mass, more preferably 0.9 to 1.5% by mass.

17. The naphtha reforming catalyst according to claim 15, wherein The crystalline form of alumina in the naphtha reforming catalyst includes one or a combination of γ-Al2O3, η-Al2O3 and θ-Al2O3; preferably, the crystalline form of alumina in the naphtha reforming catalyst is γ-Al2O3 or η-Al2O3, more preferably γ-Al2O3.

18. The naphtha reforming catalyst according to claim 15, wherein The dispersion of Pt in the naphtha reforming catalyst is 96-100%; the dispersion of Pt in the aged catalyst obtained after the naphtha reforming catalyst is treated in a hydrogen atmosphere at 700° C. for 12 hours is above 80%; the dispersion of Pt is calculated by the following formula: Where D is the dispersion of Pt.

19. Use of the naphtha reforming catalyst according to any one of claims 15 to 18 in the continuous reforming of naphtha to produce high-octane gasoline blending components or aromatics.

20. The use according to claim 19, wherein: The reaction conditions for continuous reforming of naphtha include: absolute pressure of 100KPa to 7MPa; reaction temperature of 315 to 600°C; hydrogen / hydrocarbon molar ratio of 1 to 10; liquid hourly space velocity of 0.1 to 10 hours -1 .

Citation Information

Patent Citations

  • Reforming catalyst and process

    CN103596681A

  • Macroporous alumina material preparation method

    CN105600810A

  • Synthetic method of aluminium oxide

    CN105621464A

  • Alumina carrier, preparation method thereof, dehydrogenation catalyst and application of catalyst

    CN108686713A

  • Preparation method of hydrodemetallization catalyst

    CN110935458A